AR E-books Offer a Safe, Eco-friendly Solution to Combat Oxidation in Children's Storybooks for Green Libraries - Hariyanto, Wahyu; Bahtiar, Firma Sahrul; Puspitadewi, Ganis Chandra; Mahfud, Fakhris Khusnu Reza (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
This research explores the application of Augmented Reality (AR)--based e-books as a sustainable and safe alternative to printed books within the context of green libraries. Green libraries aim to minimize environmental impact by optimizing energy use, efficient waste management, and leveraging digital resources. Although printed books remain popular in supporting children's literacy, they pose health risks due to the chemical content of materials like formaldehyde and benzene. Thus, this study evaluates the health risks associated with printed books and examines the potential of AR e-books as a safer and more eco-friendly solution for children. The method employed is a literature review, which includes product life cycle analysis, health risk evaluation, and user engagement assessment through AR technology. The findings reveal that AR e-books reduce carbon footprints and paper consumption, provide a more interactive learning experience, enhance children's reading interest, and eliminate the risks of exposure to harmful chemicals. AR e-books in green libraries can support environmental sustainability public health, and extend the lifespan of literary collections without physical degradation.